Structural analysis of action and time in sports: Judo - Marcon, G.; Franchini, E.; Jardim, J. R.; Barros Neto, T. L. (Journal of Quantitative Analysis in Sports, 2010)
Judo is an intermittent sport. As such, it is important to characterize the actions involved in combat so that training may be structured in such a way as to simulate competitive demands. However, to do so, an objective notational analysis system is necessary. The aim of the present study was to design a computer program that would aid in the analysis of time structure of specific actions during judo combat and test its inter-evaluator and intra-evaluator reliability. Ten male judokas, divided by class and category, were evaluated during three combats each. The matches were filmed and the evaluators used the computer program Saats™ (Structural Analysis of Action and Time in Sports) to analyze the following actions: break, grip, technique, fall and groundwork. The sequences were characterized by the sum of actions between each break. A total of 276 action sequences were evaluated, with a mean of 11 action sequences per combat, with four on the ground. Two evaluations were carried out by three evaluators for each judo match (inter-evaluator agreement), with only one being an expert in the software used. There was a lack of similarities in the results of only two of the variables (p<0.05). Evaluations by the same evaluator (intra-evaluator agreement) demonstrated a high reliability on all six variables. It was concluded that the use of this computer software for notational analysis in judo greatly assists in the detailing of actions performed by the athletes. The use of this software by professionals unfamiliar with it likely requires a short learning period. Knowledge of judo actions will very likely allow practitioners of the sport to be trained more specifically.